Long noncoding RNA HOXD‐AS1 induces epithelial‐mesenchymal transition in breast cancer by acting as a competing endogenous RNA of miR‐421. Issue 6 (7th February 2019) - Li, Yinyan; Han, Xu; Li, Qiaobei; Wang, Chunyan; Lou, Zhe; Wang, Xuemei
Abstract: Breast cancer (BCa) is the most common malignant tumor in females. Long noncoding RNAs (lncRNAs) are deregulated in many types of human cancers, including BCa. The purpose of the present study was to examine the expression profile and biological role of HOXD cluster antisense RNA 1 (HOXD‐AS1) in BCa. Our results revealed that HOXD‐AS1 was upregulated in BCa tissues and cell lines, and high HOXD‐AS1 expression was correlated with aggressive clinicopathological characteristics of BCa patients. Further gain‐of‐function and loss‐of‐function analysis showed that HOXD‐AS1 overexpression promoted, whereas HOXD‐AS1 knockdown inhibited BCa cell proliferation, cell cycle progression, migration, and invasion, indicating that HOXD‐AS1 may function as a novel oncogene in BCa. Mechanistically, HOXD‐AS1 could activate epithelial‐mesenchymal transition (EMT) in BCa cells. We further proved that HOXD‐AS1 might serve as a competing endogenous RNA of miR‐421 in BCa cells, and miR‐421 was downregulated and negatively correlated with HOXD‐AS1 expression in BCa tissues. Besides, we confirmed that SOX4, a master regulator of EMT, was a direct target gene of miR‐421. Further, rescue experiments suggested that miR‐421 overexpression partly abrogated the oncogenic role of HOXD‐AS1 in BCa cells. Therefore, we shed light on that HOXD‐AS1/miR‐421/SOX4 axis may be considered as a novel therapeutic target for the treatment of BCa patients.